Proceso de atención de enfermería en gestante de 26 semanas con anemia más sepsis urinaria. - Manzo Romero, Dangielie Gabriela (2020)
The purpose of this case study is to apply and develop the Nursing Care Process (PAE) in a 26-week-old 18-year-old pregnant woman with a diagnosis of Anemia plus Urinary Sepsis, using the taxonomies of NANDA, NIC and NOC. According to the information published in the National Survey on Health and Nutrition (ENSANUT-ECU 2011-2013), the prevalence of anemia in women of reproductive age is 15% nationwide. According to the information provided by the sentinel posts of the MSP's Nutrition Unit in 2012, 46.9% of pregnant women in Ecuador have anemia. For this reason, it is public health policy to supplement all pregnant women with 60 mg of elemental iron from iron, and with 400 µg of folic acid, throughout pregnancy and three months postpartum. (Ecuador, Diagnosis and treatment of anemia in pregnancy. Clinical Practice Guide, 2014). Urinary infection in pregnancy can be of different degrees of severity depending on the sector of the urinary system that is affected, the most serious being when the kidneys are affected. Pregnancy favors the appearance of urinary infections due to the hormonal changes that occur. The purpose of applying the nursing care process is to be able to provide comprehensive care through interventions that will be provided to you during your hospital stay, until your complete well-being is achieved.